Membrane Vesicles from Lacticaseibacillus Casei BL23 Exhibit Antimicrobial Activity Against Escherichia coli and Immunostimulatory Effects on Human Peripheral Blood Mononuclear Cells - D´Antoni, Cecilia; Pourtalebijahromi, Leila; Sana, Lorenzo; Dominguez Rubio, Ana Paula; Dorfner, Maja; Munkert, Jennifer; Danzer, Heike; Arnold, Philipp; Lebedev, Mikhail; Zanin, Esther; Pérez, Oscar E.; Fuhrmann, Gregor (Advanced Healthcare Materials, 2025)
Probiotics are live microorganisms known for their health benefits; however, they may pose risks for immunocompromised individuals. This study explores the potential of postbiotics, specifically membrane vesicles (MVs) derived from Lacticaseibacillus casei BL23, as a safer alternative. MVs are isolated via ultracentrifugation (UC) followed by size exclusion chromatography (SEC), revealing a mean size of 178 nm and a concentration of 2.53×1011 particles mL−1, with moderate stability over four months at 4°C. Antimicrobial assays demonstrate that SEC-isolated MVs effectively inhibit the growth of Escherichia coli DH5α. Confocal laser scanning microscopy confirms the internalization of MVs by both E. coli and macrophages. Additionally, MV treatment elicits a significant immune response, marked by increased levels of pro-inflammatory cytokines (TNF-α, IL-6, IL-8, IL-1β) alongside IL-10 production in peripheral blood mononuclear cells. Importantly, cytotoxicity assays indicate that MVs are non-toxic to these cells and preserve epithelial barrier integrity in Caco-2 cell monolayers. MVs showed a trend towards extending lifespan in the Caenorhabditis elegans in vivo model upon infection with Pseudomonas aeruginosa. These findings underscore the dual-activity potential of L. casei BL23 MVs as effective tools for combating infections while enhancing immune function, offering a promising strategy to address antibiotic resistanc